The factors that influence the oral health-related quality of life in 12-year-old children: baseline study of a longitudinal research - Ling Sun; Hai Ming Wong; Colman P. J. McGrath (Health and Quality of Life Outcomes, 2017)
Abstract Background Oral health-related quality of life (OHRQoL) could be affected not only by oral health but also by demographic and ecosocial factors. This research aimed to analyze the sociodemographic and clinical factors that may influence the OHRQoL of 12-year-old children. Methods A representative sample was selected from Hong Kong. Periodontal status and caries were examined according to WHO criteria. Four orthodontic indices were used to assess malocclusion. Child Perception Questionnaires (CPQ11–14-ISF:8 and CPQ11–14-RSF:8) including four domains, namely oral symptoms (OS), functional limitations (FL), emotional well-being (EWB), and social well-being (SWB), were used to measure OHRQoL. Adjusted OR was calculated by ordinal logistic regression. Results Totally 589 eligible subjects (305 females, 284 males) were recruited. Males tended to rank higher in OS domain but lower in EWB domain (adjusted OR = 1.89 and 0.67). Mother’s education was linked more closely with children’s CPQ scores. Higher education levels were associated with better quality of life (adjusted OR = 0.45 and 0.37). Household income showed no effect on CPQ scores. Unhealthy periodontal conditions had a negative effect on EWB and total CPQ (adjusted OR = 1.61 and 1.63). High caries experience only had a negative effect on SWB (adjusted OR = 1.60). Malocclusion affected FL, EWB, SWB and total CPQ: all malocclusion severities affected SWB; only severe malocclusions affected FL, EWB and total CPQ. Conclusion Males were more tolerant of oral symptoms than females were. Higher levels of mother’s education led to better OHRQoL of their children. Unhealthy periodontal conditions affected emotional well-being, while high caries experience affected social well-being. All malocclusion severities had an effect on social well-being; severe malocclusion further caused functional limitations, worse emotional well-being, and hence worse OHRQoL.